Enantiomer separation by enantioselective inclusion complexation-organic solvent nanofiltration - Ghazali, Nazlee Faisal; Ferreira, Frederico C.; White, Andrew J. P.; Livingston, Andrew (Elsevier, 2006)
A novel chiral separation process, which utilizes a combination of enantioselective inclusion complexation (EIC) and organic solvent nanofiltration (OSN), was developed. Although EIC is an attractive way to resolve racemates, the difficulties associated with enantiomer recovery and chiral host recycle has limited large-scale applications. EIC coupled with OSN replaces distillation for the recovery of enantiomers from enantioenriched solid complex. A decomplexation solvent is employed to dissociate enantiomers from the complex, and subsequent separation of enantiomers from the chiral host is realized using OSN. The new process was investigated using racemic 1-phenylethanol as the guest and (R,R)-TADDOL as the chiral host. This novel technology expands the application of EIC to the resolution of nonvolatile racemates , and enables large-scale application.